2013
DOI: 10.1111/nph.12286
|View full text |Cite
|
Sign up to set email alerts
|

Geminivirus Rep protein interferes with the plant DNA methylation machinery and suppresses transcriptional gene silencing

Abstract: SummaryCytosine methylation is an epigenetic mark that promotes gene silencing and plays an important role in genome defence against transposons and invading DNA viruses. Previous data showed that the largest family of single-stranded DNA viruses, Geminiviridae, prevents methylation-mediated transcriptional gene silencing (TGS) by interfering with the proper functioning of the plant methylation cycle.Here, we describe a novel counter-defence strategy used by geminiviruses, which reduces the expression of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 57 publications
3
94
0
7
Order By: Relevance
“…Generation of TYLCSV C2 T2C (ΔC2), C4 T2C (ΔC4), V2 T2G (ΔV2) mutant clones are described elsewhere3436. The TYLCSV ΔC3 mutant (containing a 72 bp deletion) was generated by two-sided splicing overlap extension37 using pGTYA14 as template and two primer pairs for the two initial PCRs: ΔC31F/ΔC31R (5′-CGAAAGCCGCGGATGTAC-3′/5′-AATGAGGCTAGCGTTACCTTGAGAACACAATAGATG-3′) and ΔC32F/ΔC32R (5′-GGTAACGCTAGCCTGATTCTTATACACTTGAAACCTAAAG-3′/5′-GGAGGCATACCCACTATC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Generation of TYLCSV C2 T2C (ΔC2), C4 T2C (ΔC4), V2 T2G (ΔV2) mutant clones are described elsewhere3436. The TYLCSV ΔC3 mutant (containing a 72 bp deletion) was generated by two-sided splicing overlap extension37 using pGTYA14 as template and two primer pairs for the two initial PCRs: ΔC31F/ΔC31R (5′-CGAAAGCCGCGGATGTAC-3′/5′-AATGAGGCTAGCGTTACCTTGAGAACACAATAGATG-3′) and ΔC32F/ΔC32R (5′-GGTAACGCTAGCCTGATTCTTATACACTTGAAACCTAAAG-3′/5′-GGAGGCATACCCACTATC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the AC2/AL2 proteins encoded by cabbage leaf curl virus and tomato golden mosaic virus, the C2/L2 proteins encoded by beet curly top virus and beet severe curly top virus, and the bC1 protein encoded by tomato yellow leaf curl China betasatellite (TYLCCNB) can decrease DNA methylation and suppress TGS by interfering with the methyl cycle (Buchmann et al, 2009; Yang et al, 2011;Zhang et al, 2011). A recent report indicated that geminivirus replication-associated protein (Rep, also known as C1, AL1 or AC1) could also suppress TGS by reducing the expression of plant DNA methyltransferases (Rodríguez-Negrete et al, 2013).Tomato yellow leaf curl virus (TYLCV) is a member of the genus Begomovirus and contains a single genome component with six open reading frames (ORFs). Two ORFs (V1 and V2) are located on the viral strand and the other four ORFs (C1, C2, C3 and C4) are on the complementary strand (Zhang et al, 2009).…”
mentioning
confidence: 99%
“…Viral mRNAs are subject to PTGS (34,35), while methylation-mediated TGS targets viral minichromosomes (36,37). As a counterdefense, geminiviruses and associated satellite DNAs encode pathogenicity factors that employ multiple mechanisms to suppress both PTGS and TGS and inhibit repressive methylation (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The hypersensitivity of methylation-deficient mutant plants to geminivirus infection and the existence of numerous viral countermeasures underscore the defensive value of viral chromatin methylation.…”
mentioning
confidence: 99%